Rifampicin for Treatment of Cholestatic Pruritus Caused by Drug-Induced Acute Liver Injury as Assessed by the RUCAM Classification - Ali R. Ahmadi; Maria Chicco; Marcel van den Berge (Case Reports in Hepatology)
A male bodybuilder of 39 years of age developed severe pruritus, nausea, and jaundice after injecting anabolic steroids purchased on the black market. The patient had no history of liver disease and no risk factors for viral hepatitis. Extensive laboratory testing, radiographic imaging, and liver biopsy excluded a majority of potential pathologies. The patient was diagnosed with drug-induced acute liver injury and secondary acute renal failure most likely caused by testosterone purchased on the black market. The pruritus caused insomnia and significant psychological distress. Treatment was initiated with cholestyramine and naltrexone for one week with no effect on the pruritus. Subsequently, all medications were stopped, and rifampicin was started. Pruritus resolved after starting rifampicin, and liver and kidney function improved rapidly and normalized within 5 months.